The ancient Near East ; vol 1 an anthology of texts and pictures - Pritchard, James B. (Princeton, NJ Princeton UP, 1958)
Includes bibliographical references and indexes, maps and photographs.
Keywords: Bible. O.T. -- history of contemporary events